RESPON PELAKU UMKM TERHADAP DIGITALISASI ADMINISTRASI PAJAK : STUDI GROUNDED THEORY - Muslimah Hamidah; Mubaraq Raihan Muhammad (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the responses of UMKM actors to the digitalization of tax administration in Indonesia using a qualitative grounded theory approach. Data were collected through in-depth interviews, observations, and field notes involving 10 UMKM actors from various sectors. The results show that initial responses were ambivalent, characterized by confusion, fear of making input errors, and low digital literacy. However, these responses gradually shifted toward acceptance following positive experiences and external support such as training. Factors influencing adaptation include digital literacy, perceived ease of use, social support, and technical constraints. Adaptation strategies include self-learning, seeking assistance from others, and participating in tax socialization programs. This study produces a substantive theory that the acceptance of tax digitalization occurs gradually and is influenced by both internal and external factors.